Produção de pólen apícola e sua avaliação nutricional, em Araguaína-TO - Almeida, Edésio da Silva (Universidade Federal do Tocantins, 2023)
Beekeeping is still carried out by a very small portion in the North region of the country, because of several factors, among them, the lack of public incentive to exercise the activity, the climate, the lack of adequate management techniques to have a greater colony production of bee products, mainly honey and other bee products (Pollen, apitoxin jelly and others), which may have an even greater value than honey, as we do not know the real value of their nutritional properties, being foods producing in two of the areas with one of the greatest diversity of flora in the world. . The experiment was conducted at the School of Veterinary Medicine and Animal Science (EMVZ) at the Federal University of Northern Tocantins. being divided into two parts: the first was the evaluation of bee pollen production during the months of April to October 2021, being the months the treatments, totaling seven and six hives the repetitions and the second, evaluation of the bromatological composition of the samples , regarding crude protein (CP), crude fiber (FB), Ethereal Extract ash, total dry matter (DM), total carbohydrates (CHO) and gross energy (EB). Analysis of variance followed by the Scott-Knott cluster test (1974). From the data obtained, the production of bee pollen in the Cerrado Amazon transition region is viable, with average daily pollen productivity ranging from 72.28 g in May to 24.93 g in October. The average honey production in the period was 20.55 kg hive-1. There was no significant difference for lipids, which ranged from 6.67% to 4.04%, but there were variations in CP of 27.42% and 20.38%, in ash contents from 3.55% to 2.23%. There were statistical variations in the levels of total carbohydrates, from 70.01% in October to 59.41% in June. The bee pollen in the region has a considerable amount for commercialization and nutritional quality in its composition, in accordance with current legislation. The only item that fluctuated was the crude fiber in the months of April and October, with a difference of 0.84% and 0.90%, respectively, while for those in the dry season it varied from 11.61% and 8.53%.